Michèle Le Doeuff's "Primal Scene": Prohibition and Confidence in the Education of a Woman - Anderson, Pamela Sue (Text Matters: A Journal of Literature, Theory and Culture, 2011)
My essay begins with Michèle Le Doeuff's singular account of the "primal scene" in her own education as a woman, illustrating a universally significant point about the way(s) in which education can differ for men and women: gender difference both shapes and is shaped by the imaginary of a culture as manifest in how texts matter for Le Doeuff. Her primal scene is the first moment she remembers when, while aspiring to think for herself, a prohibition is placed in her reading of literature. Her philosophy teacher—at a boys' school—told the young Michèle that Kant's Critique of Pure Reason was "too difficult" for her to read. In recalling this scene, the older (and wiser) Michèle—now, a woman philosopher—directs her readers to this text by Kant, in order to demonstrate how knowledge has been constrained by the narrative and imagery in the text of a philosopher; similarly, in the texts of others. She finds the central imagery of Kant's text for setting the limits to human knowledge in his account of "the island of understanding," or "land of truth," surrounded by "a stormy sea" of uncertainty; the latter image also retains a seductive appeal, threatening to destroy the confidence of any knower who ventures out beyond the well-marked out island. Moreover, women have (too) often been associated with the dangers at sea beyond the safety of the island, where falsehood and worse reign. I propose that "text matters" here not only for gender issues, but for the postcolonial theory which Le Doeuff's reading of island imagery enhances in western literature and culture. The suggestion is that women in the history of ideas have been more susceptible than men to prohibitions (to reading texts): women's negative education is against going beyond certain boundaries which have been fixed by a generally colonialist culture on the grounds of gender-hierarchies. I stress the significance of confidence in the production of knowledge. A lack or an inhibition of confidence in one's own ability to think critically risks the damaging exclusions of, for example, colonialism and sexism. My aim is to unearth the political biases evident in textual imagery, while also pointing to new epistemic locations, with island-and-sea imagery that transgresses patriarchal prohibition, liberating subjects for confident reading and writing of texts today.